Fabrication of Superhydrophobic Self-Cleaning Coatings by Facile Method: Stable after Exposure to Low Temperatures and UV Light - Toktarbaiuly, O.; Kurbanova, A.; Ualibek, O.; Seralin, A.; Zhunussova, T.; Sugurbekova, G.; Nuraje, N. (KU Publ., 2022)
Self-cleaning hydrophobic surfaces attracted public attention last few decades after discovering of lotus effect. Ability of lotus leaves to keep cleanness in relatively dirty places and to clean up itself during rains directed to the development of novel materials and surface structure modification. The surface with such smart properties may have the potential for cost-effectiveness in the case of application in skyscrapers, high buildings, etc. Two main criteria for the surface to express hydrophobic behavior are roughness and low surface energy of the coating material. In this study, superhydrophobic self-cleaning coatings were prepared by a simple, facile, and cheap method using easily available materials, such as polydimethylsiloxane (PDMS) and TiO2 nanoparticles, and fully characterized for direct usage. PDMS is a bonding layer and TiO2 nanoparticles are a reinforced composite to form roughness, which shows superhydrophobicity. Characterizations showed that the prepared superhydrophobic coating has a water contact angle of up to 165.5°, with sliding angle of less than 5º. Also self-cleaning and surface microfluidic properties have been studied. The superhydrophobic properties of these coatings do not change even after exposure to their surface to low temperatures and UV light. SEM images confirm the rough structure of obtained surface on glass and sand grains.
Жеңіл әдіспен төмен температура мен ультракүлгін сәулесінің әсерінен кейін тұрақты супергидрофобты өзін-өзі тазартатын жабындарды дайындау
Получение супергидрофобных самоочищающихся покрытий легким методом: устойчивых к воздействию низких температур и ультрафиолетового излучения
Keywords: superhydrophobic coating; superhydrophobic sand; polydimethylsiloxane; titanium oxide nanoparticles; contact angle; UV light; facile method; electrokinetic potential